Effect of hysteroscopic examination on the outcome of in vitro fertilization - Trninić-Pjević Aleksandra; Kopitović Vesna; Pop-Trajković Sonja; Bjelica Artur; Bujas Irena; Tabš Dunja; Ilić Đorđe; Stajić Dragan (Vojnosanitetski Pregled)
Bacground/Aim. Implantation failure after embryo transfer is one of the main problems of in vitro fartilization (IVF) and intrauterine pathologies can lead to unsuccessful outcome. The aim of this study was to determine if hysteroscopic examination of uterine cavity and consequent treatment of intrauterine lesions prior to IVF could improve the pregnancy rate in women under 38. Methods. This study included 480 patients under 38, who had undergone IVF or IVFICSI - embryo transfer cycles, in which one or more good quality embryos were transferred. By transvaginal sonography performed within the past 2 months, the uterus was found normal in all the patients enrolled in our IVF unit. The patients were divided into three groups: group A - with no hysteroscopic evaluation and no pathology, group B - with hysteroscopy but no pathology, and group C - with abnormal hysteroscopy finding and corresponding treatment. Results. The obtained results revaled no difference in the mean age, duration of infertility, number of mature oocytes in either group (p > 0.05). Clinical pregnancy rates in the groups A, B and C were 36.9%, 58.75% and 32.7%, respectively, and delivery rates were 27.5%, 48.7% and 25.7%, respectively. There was a statistically significant difference among the groups concerning pregnancy and delivery rates. Conclusion. Considering the results of this study we could conclude that hysteroscopy, as a routine examination, should be performed before the first IVF-ET cycle in all patients thereby reducing the failures and then the costs of IVF-ET.